Blended Learning for Stoichiometry and Mass Balance in Environmental Chemistry - Hadibarata, Tony; Hidayat, Topik; Khamidun, Mohd Hairul (Tecno Scientifica Publisher, 2025)
Teaching environmental chemistry today involves both conventional and digital learning modes. Traditional approaches such as lectures, problem-solving, and laboratory exercises, offer content that is more or less structured with direct interaction, but not active engagement, interactivity, and enough resources are often found wanting. To better learn the subject, blended learning has been introduced, including some important digital tools like online facilities, simulations, and virtual labs. These ensure access and increase participation but the major con that students show low motivation because of the unequal access to the tools, the challenge that teachers face using the new tools, low student motivation, and problems in assessment. Its use has grown, but the effectiveness of blended learning, especially in stoichiometry and mass balance, which are considered to be rather complex, is not well documented. This review aimed to answer how traditional, digital, and blended learning approaches work in environmental chemistry education and what the benefits and challenges of each are. While traditional methods are more inclined to encourage the interaction of the instructor, which already appears to be passive and sometimes disconnected from the real situation outside the classroom, the blended learning method will put forward greater interactivity and personalization, though much will now depend on the individual student and the access to technology. A balanced approach will be evidenced by blended learning, with the strong points imbibed from both the modes, but, however, much intelligence is required to apply it to steer clear of further weaknesses. For improvement in the teaching of Environmental Chemistry, it is essential to invest in the digital infrastructure, faculty training, strategies of student engagement, and innovative models of assessment. If applied strategically, then blended learning can bridge effectively between theory and practice, making the teaching of Environmental Chemistry more engaging, inclusive, and outcome-based.